Pembinaan Prestasi Cabang Olahraga Hoki di Kabupaten Kudus (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this study was to find out the implementation achievement development of Hockey Sports in Kudus Regency. This research uses a qualitative etnographic approach. Data collection using the method of observation, interviews, and documentation. The subjects in this study were administrators, coaches, and athletes. The data analysis technique used is data triangulation technique. Data analysis with data reduction, data presentation, and drawing conclusions. The results of the research, it can be concluded that the implementation achievement development of Hockey Sports in Kudus Regency is good enough, it can be seen from the aspects of pemassalan, nurseries, achievements, organizations, training programs, human resources, facilities and infrastructure as well as funding.. From the results of the research, it can be concluded that the implementation achievement development at the Hockey Kudus is good enough, it can be seen from the aspects of pemassuran, nursery, achievement, coaching, human resources, training programs, facilities and infrastructure as well as funding